Legislação urbana e ambiente construido : uma abordagem sistemica dos parametros de controle de uso e ocupacao do solo em Fortaleza - Hissa, Francisco Nasser (2005)
This work analyzes the efficiency of the instruments used to control land use and occupation in the Fortaleza legislation. The approach considers the objectives to be achieved and the limitations imposed by them on the project activity.